2011
DOI: 10.1080/09658211.2011.558512
|View full text |Cite
|
Sign up to set email alerts
|

TV or not TV? Does the immediacy of viewing images of a momentous news event affect the quality and stability of flashbulb memories?

Abstract: The flashbulb accounts of 38 participants concerning the September 11th 2001 terrorist attack reported at both 28 hours and 6 months following the event were examined for quantity, quality, and consistency as a function of the time lapse between first learning of the event and initial viewing of media images. The flashbulb accounts of those who reported seeing images at least an hour after learning of the event differed qualitatively, but not quantitatively, from accounts of participants who reported seeing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Three of them were obtained from previous studies (e.g., Bohn & Berntsen, 2007; Conway et al, 1994; Kensinger & Schacter, 2006a) and asked participants to indicate: (A) how much they followed the media coverage of the referendum result in the past week, (B) how much they thought about the referendum since finding out the results, and (C) how much they talked about the referendum with their friends/family and colleagues. We also expected that many participants relied on the Internet to gather information (Hirst et al, 2009; Luminet et al, 2004; Schaefer et al, 2011) and therefore added one more question: how much they spent on the Internet reading the latest news about the referendum in the past week. For all questions, participants were asked to indicate the most appropriate option on a scale ranging from 1 ( rarely or none of the time or less than 1 day ) to 5 ( daily ).…”
Section: Methodsmentioning
confidence: 99%
“…Three of them were obtained from previous studies (e.g., Bohn & Berntsen, 2007; Conway et al, 1994; Kensinger & Schacter, 2006a) and asked participants to indicate: (A) how much they followed the media coverage of the referendum result in the past week, (B) how much they thought about the referendum since finding out the results, and (C) how much they talked about the referendum with their friends/family and colleagues. We also expected that many participants relied on the Internet to gather information (Hirst et al, 2009; Luminet et al, 2004; Schaefer et al, 2011) and therefore added one more question: how much they spent on the Internet reading the latest news about the referendum in the past week. For all questions, participants were asked to indicate the most appropriate option on a scale ranging from 1 ( rarely or none of the time or less than 1 day ) to 5 ( daily ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the diagnosis news itself may be similarly surprising and consequential across patients, there may be significant differences in how news of a diagnosis is delivered , depending on the medical professional. Prior work has shown that news source can influence how an event is remembered (Bohannon, Gratz, & Cross, 2007; Schaefer, Halldorson, & Dizon‐Reynante, 2011; Schmolck et al, 2000; Talarico, Kraha, Self, & Boals, 2019). In the current study, we expand these findings to determine whether the way in which the news is delivered is related to the likelihood and persistence of a FBM.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism to explain the “TV priority” in remembering (Neisser et al, 1996) is the increased salience of vivid images displayed during news broadcasts. Schaefer et al (2011) compared individuals who saw images as they learned the news, those who saw images immediately after learning the news, and those who waited at least an hour before viewing images on various measures of flashbulb memory. They found that although the delayed viewing group did not differ from the simultaneous or immediate viewing groups in the number of canonical details reported (i.e., “time; location; ongoing activity; informant; presence of others; clothes worn by the participant; first thought; feelings; [and] subsequent activity,” pp.…”
Section: Inaccuracies In Flashbulb Memoriesmentioning
confidence: 99%